Factors influencing the determination of dosing weight in the neonatal intensive care unit (NICU) - Cassandra R. Montoya; Janine Y. Khan; Delphine Nelson; Gustave Falciglia (Scientific Reports)
Abstract The objective of this study is to describe the properties of dosing weight in the neonatal intensive care unit (NICU). Infants were identified from a database of very low birth weight infants. Before regaining birth weight (BW), dosing and birth weight% difference was described. After regaining BW, dosing and measured weight% difference and frequency of dosing weight updates were described. Associations with infant characteristics including comorbid conditions, serum biochemistries, fluid intake, and urine output were evaluated. There were 115 infants over 4,643 infant-days with a median BW of 1060 g (interquartile range [IQR]: 750, 1300) and median time to regain BW of 10 days (IQR: 8, 13). After regaining BW, dosing weight was 4.2% less than measured weight. The gap widened with increasing creatinine and narrowed with increasing urine output. The only factor associated with the frequency of dosing weight updates was day of the week. Dosing weights in the NICU appear to fall into one of three categories: BW prior to regaining BW, practical weight to facilitate medication and nutrition ordering, and “dry” weight, adjusting for fluid overloaded states. We recommend using measured weight to avoid a 4% daily loss in nutrition intake once BW is regained.